THE STUDY OF ADO 26/DF AND MI 4733 IN THE FEDERAL SUPREME COURT AND THE CRIMINALIZATION OF TRANSPHOBIA: Notes on constitutionalism and democracy - dos Santos de Assis, Nery; Rosa Neto, Fabio; Walmott Borges, Alexandre (Revista de Estudos Jurídicos da UNESP, 2025)
The development of this research was due to the political scenario recently experienced in Brazil, of distrust of institutions, in which discussions between the limits of action of the Three Powers once again gained prominence. The time was marked by the judgment of the Direct Action of Unconstitutionality by Omission (ADO) 26 and the Writ of Injunction (MI) 4733, which aimed to criminalize conduct by the Judiciary due to the lack of protection for constitutional principles, such as equality. Given this, the research seeks to answer the following question: How did the Court position itself, under the dilemma between the Separation of Powers and the democratic deficit of judicial review, in the judgment of ADO 26 and MI 4733 for the criminalization of homophobic and transphobic practices? The hypothesis is that the Federal Supreme Court justices adopt a material conception of the concept of democracy, and use the method of constitutional interpretation to avoid criticism of the violation of the Principle of Separation of Powers by the Judiciary. In order to confirm (or not) the hypothesis, the work was carried out through descriptive and qualitative documentary research, comparing the bibliography developed in the area and using the analytical method applied to reading the research problem. he object of this research is to analyze the limits of the judiciary’s action as an agent in the creation of legal norms that typify conduct within the scope of criminal law, through constitutional actions in the face of the normative absence and inaction of the Legislative Power within constitutional democracies, in particular in the Brazilian case, through the action of the STF in ADO 26/DF and in MI 4733 in the judgment of transphobia against the LGBTQIA+ community. The work was developed through descriptive and qualitative documentary research, compared to the bibliography developed in the area, the method was analytical applied to the reading of the problem object of the research.